The politics book - DK Publishing, Inc (New York DK Pub, 2013)
"Exploring more than 100 big ideas on topics as diverse as the rule of law, the extent of liberty, and the justification of warfare, [this book] takes you on a journey through the history of politics, from the influential theories of ancient Greece, Rome, and Asia to modern concepts voiced by today's brightest political thinkers."--Front jacket flap
Ancient political thought, 800 BCE-30 CE -- Medieval politics, 30 CE-1515 CE -- Rationality and enlightenment, 1515-1770 -- Revolutionary thoughts, 1770-1848 -- The rise of the masses, 1848-1910 -- The clash of ideologies, 1910-1945 -- Postwar politics, 1945-present
Includes index
1
Keywords: Political science -- History; Political science; World politics